Merancang Administrasi Sekolah Dasar untuk Mendukung Peningkatan Mutu Pendidikan - Adilah Nurazani; Ali Mustopa Yakub Simbolon; Rahmi Simanjuntak; Farhan Farhan; Mutia Safitri (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
School administration is a fundamental component in ensuring effective and high-quality education in elementary schools. This study aims to describe the concept of effective school administration, the essential administrative components that must be designed and managed, and the factors influencing its success in supporting educational quality improvement. A qualitative approach was employed, focusing on naturally occurring administrative processes within elementary educational institutions. Data were obtained through literature review on the management of curriculum, students, educational staff, finance, facilities, and school–community relations. The findings indicate that effective school administration must be carried out systematically through core management functions, including planning, organizing, implementing, and monitoring. The success of school administration is strongly influenced by the leadership of the principal, the competence of teachers and staff, the utilization of information technology, accountable financial management, adequate facilities, and community participation. Therefore, strengthening school administration becomes a key strategy in creating an orderly, efficient, and student-oriented educational process to improve learning quality in elementary schools.